New Black Queer Cinema - Wallenberg, Louise (New Queer Cinema: A Critical Reader, 2004)
In 1989, three years before the New Queer Wave was even invented or discovered, two very different yet interconnected films were produced on either side of the Atlantic. Both soon became critically successful and both would win a number of prizes at different international film festivals and venues. In retrospect, these two films have come to constitute the very incitement to the Wave. British filmmaker Isaac Julien’s Looking for Langston premiered in early 1989 and American filmmaker Marlon Riggs’s Tongues Untied premiered later that same year, the latter including a still photo from the former so as to pay homage
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Our Stories Have Never Been Told: Preliminary Thoughts on Black Lesbian Cultural Production as Historiography in The Watermelon Woman - Richardson, Matt (Black Camera, 2011)
Cheryl Dunye's 1996 film The Watermelon Woman earned a place in cinematic history as the first feature-length narrative film written and directed by an out black lesbian about black lesbians. This article examines how the film provides an important opportunity to mark the burgeoning genre of black queer documentary as a historiographical medium. The documentary film is a tool that highlights underexplored issues in black experience and provides a cultural site for imagining new possibilities for black lesbian subjectivity and creating innovative approaches to representing sexuality in black filmmaking.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

Pink Dollars: Gay and lesbian Film Festivals and the Economy of Visibility - Rhyne, Ragan (2007)
This dissertation is about gay and lesbian film festivals, the first of which was founded in San Francisco in 1977 and subsequently served as a model for their international proliferation over the next thirty years. While the films programmed in these festivals have received a great deal of attention from scholars and critics, the festival institution itself has received less consideration. This dissertation narrates the history of gay and lesbian film festivals through an economic lens, asking how fundraising practices have been deployed in the community building projects of festivals, how the administrative structures of festivals as nonprofit organizations have been leveraged by the state toward the management of new social movements, and how these nonprofits have participated in the identification and cultivation of populations as niche markets by the commercial sector. This historical schema will offer an alternative model for understanding queer image production, not through a textual analysis of those images, but through an examination of the material circumstances of their circulation and distribution. This dissertation is not simply about the ways that community organizations like film festivals have been strategically engaged by the state and the market in the management and exploitation of gays and lesbians, it argues that gays and lesbians themselves have articulated their politics, artistic practice, and discourse of community within (and against) the parameters defined by the demands of organizational sustainability. Furthermore, this dissertation will illustrate why taking economic activity seriously as a part of the material practices of queer image production answers crucial questions about the ways that sexuality operates as a category of governance. The history of gay and lesbian film festivals, and their regulation through the administrative structures of the nonprofit sector, is part of a much larger history of political struggle and the development of new social movements over the past three decades.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude de la réception; 2-Étude des industries culturelles; 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Struggles for Representation: African American Documentary Film and Video - Reid, Mark A. (American Literature, 2000)
Struggles for Representation examines over 300 non-fiction films by more than 150 African American film/videomakers and includes an extensive filmography, bibliography, and excerpts from interviews with film/videomakers. In eleven original essays, contributors explore the extraordinary scope of these aesthetic and social documents and chart a previously undiscovered territory: documentaries that examine the aesthetic, economic, historical, political, and social forces that shape the lives of black Americans, as seen from their perspectives.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Lesbian "Making-of" Documentaries and the Production of Lesbian Sex - Hankin, Kelly (The Velvet Light Trap, 2004)
The Velvet Light Trap 53 (2004) 26-39 On December 2, 2001, HBO began airing Project Greenlight, a twelve-part documentary series chronicling the production of a feature film by novice writer-director Pete Jones. With its spectacle of backroom dealings, unchecked egos, and human frailties, the television series capitalized on the contemporaneous success of like-minded "reality" programs such as Survivor and Temptation Island. Perhaps more closely, Project Greenlight also tapped into the current vogue for the "behind-the-scenes" and the "making-of" genres, represented by straight-to-video titles such as Star Trek-Deep Space Nine: Behind the Scenes (1993), Making of Jurassic Park (1995), and The Matrix Revisited (2001), television programs such as the Sundance Channel's Anatomy of a Scene, HBO's First Look, and MTV's Making the Video, and the proliferation of behind-the-scenes and making-of packaging on DVDs. A reflection of the growth of film-related ancillary products in the 1980s, the ever-expanding Hollywood ego, and the demands of a twenty-four-hour television cable market, the increased appearance of the making-of documentary format no doubt also reflects the renewed interest in amateur filmmaking promulgated by the age of desktop video. Perhaps as a manifestation of this interest, making-of documentaries have become increasingly more detailed in their coverage. Whereas the 1981 television special The Making of "Raiders of the Lost Ark" (Phillip Schuman) focuses mostly on the film's stunt work, special effects, location shoots, and set design, the recently released making-of documentary The Matrix Revisited focuses on script development, preproduction, production, postproduction, and exhibition, introducing viewers to costume designers, storyboard artists, and editors along the way. This attention to production detail can also be seen in Sundance's Anatomy of a Scene, which hones in on the construction, from music to costume to camera work, of a single scene. And certainly raising the bar on the level of detail included in the making-of genre is Project Greenlight, which is a "warts-and-all" look at film production, from squabbles over budgets to catering fiascos. Despite the making-of video's increased attention to the minutiae of filmmaking, one of the areas that remains outside the purview of most Hollywood making-of documentaries is the production of sex. Discussions about the cinematic logistics of creating a sex scene—how, when, and with what resources—are usually not featured in making-of documentaries. Of course, given our celebrity-driven culture, the question of sex vis-à-vis film production, particularly a Hollywood film production, is hardly absent from the publicity that surrounds a film. It is not uncommon to hear actresses or actors discussing what it was like to kiss another actor on the set. But these kinds of concerns are usually the province of entertainment magazines and television, not the province of ancillary related products such as the making-of video. While stories of roles requiring nudity or sex scenes abound on television shows such as Access Hollywood, Entertainment Tonight, and E! News Daily,these kinds of topics are less likely to appear in production-generated documentaries. Indeed, while the production of the provocative sex scene between Halle Berry and Billy Bob Thornton in Monster's Ball (Marc Forster, 2001) generated much discussion on television entertainment programs, talk shows, and newsmagazines, it was the film's prison execution sequence that was featured in the Sundance Channel's making-of special on the film. Given the lack of focus on sex scenes in most making-of documentaries, it is interesting to note that the two existing making-of documentaries for lesbian-made, lesbian-themed feature films—The Making of Bar Girls (1995) and Moments: The Making of Claire of the Moon (1992)—both heavily focus on the production of lesbian sex. Moreover, both lesbian making-of documentaries emphasize the cast's and the crew's sexual titillation over the creation of sexual sequences. In this essay I look at what this strategy reveals about the collective climate and concerns of lesbian feature filmmaking in the United States today.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

"Just Because I'm a Lesbian Doesn't Mean I'm Evolved" The "Bad Queer" Women's Comedic Web Series - San Filippo, Maria (Velvet Light Trap, 2020)
The queer women's comedic web series that have flourished in the last decade, serving as launching pads for their creators, coincided with media-industry nichification's segmentation of a consumer population regarded by advertisers and content providers as one monolithic LGBTQ community. The series I examine-from The Slope, which premiered in 2010, to Strangers, released in 2017-voice their creators' and characters' marginalization from and even opposition to such an imagined community, through recourse to what I call a "bad queer" rhetorical practice, which uses ironic metacommentary to critique assimilationist values and tropes alongside queer identity policing. These series emerged, at least initially, as an alternative sphere of queer media production and a queer discursive mode that employs disidentification as a politicized strategy to challenge dominant LGBTQ scripts. Offering an irreverent alternative to mainstream and millennial LGBTQ cultural products, these "bad queer" web series express the plurality of the queer "community" and expose political contestations within its ranks, and in so doing serve as brand differentiation for a new generation of queer media producers.
Keywords: 1-Cinéma; 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créatrice; _Nettoyé

We are here but are we Queer?: Lesbian Filmmaking versus Queer Cinema Conference, London, 12 March 1994 - Florence, Penny (Screen, 1994)
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; _Nettoyé

The Desiring-Image: Gilles Deleuze and Contemporary Queer Cinema/Ethereal Queer: Television, Historicity, Desire - Betancourt, Manuel (Film Quarterly, 2013)
Betancourt reviews The Desiring-Image: Gilles Deleuze and Contemporary Queer Cinema by Nick Davis and Ethereal Queer Television, Historicity, Desire by Amy Villarejo.
Keywords: 1-Cinéma; 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des industries culturelles; 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

The View from here Conversations with Gay and Lesbian Filmmakers - Hays, Matthew (Arsenal Pulp Press, 2007)
The history of gay and lesbian cinema is a storied one, and became that much larger with the recent success of Brokeback Mountain. But the history of gay and lesbian filmmakers is its own story. In The View From Here, queer directors and screenwriters speak passionately about the medium, in particular their personal experiences navi-gating the often cynical and cruel film industry. All of them offer fascinating anecdotes and ideas about cinema, and speak candidly about their attempts to combat studio apathy and demands of “the market” to create films that are entertaining, engaging, and truthful.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice LGBTQ+; _Nettoyé

Identity and Performance in Yvonne Welbon’s Remembering Wei-Yi Fang, Remembering Myself: An Autobiography - Heitner, Devorah (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
In novel ways, and from a surprising location, Yvonne Welbon’s Remembering Wei-Yi Fang, Remembering Myself: An Autobiography (1995) explores some of the same dilemmas that earlier African American expatriate artists promulgated, using their time abroad as a win dow onto America, while relishing the nurturing possibilities of partial escape from American racism. Some of the most complex and insightful observations about America and American racism have been crafted by African American expatriate artists such as James Baldwin and Josephine Baker. These artists’ depictions of their encounters abroad complicate our understandings of American identity and American racism.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Identités diasporiques; _Nettoyé

Producing Black Lesbian Media - Moore, Candace (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
In interviews the comedian Wanda Sykes describes being a successful black, openly gay woman in Hollywood as akin to being a unicorn. Clearly Sykes is majestic. Yet her joke hinges on a bitter truth: the mainstream media industry grants few women, not to mention lesbians of color, access to power. Despite shifts in the cultural imaginary around civil rights, Hollywood continues to maintain an embarrassing lack of diversity in its labor force, especially at decision-making levels. To battle this long-standing reputation, studios have developed diversity-hiring programs.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

Shine Louise Houston: An Interstice of Her Own Making - Stallings, L. H. (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
It is the twenty-first century, and there is a black lesbian director and producer making pornography! Porn, a genre of film and media that in the last quarter of the twentieth century many black feminist lesbians viewed as capable only of representing and manifesting violence, abuse, and shame. In this essay I examine one of the early works of the black lesbian filmmaker Shine Louise Houston, In Search of the Wild Kingdom (2007), to explore how and why we have arrived at what is a transition from Blues Legacies and Black Feminisms to Pink and White Productions, and from New
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

Hollywood at the Intersection of Race and Identity - Konzett, Delia Caparoso. (Rutgers University Press, 2020)
Hollywood at the Intersection of Race and Identity explores the ways Hollywood represents race, gender, class, and nationality at the intersection of aesthetics and ideology and its productive tensions. This collection of essays asks to what degree can a close critical analysis of films, that is, reading them against their own ideological grain, reveal contradictions and tensions in Hollywood’s task of erecting normative cultural standards? How do some films perhaps knowingly undermine their inherent ideology by opening a field of conflicting and competing intersecting identities? The challenge set out in this volume is to revisit well-known films in search for a narrative not exclusively constituted by the Hollywood formula and to answer the questions: What lies beyond the frame? What elements contradict a film’s sustained illusion of a normative world? Where do films betray their own ideology and most importantly what intersectional spaces of identity do they reveal or conceal?
Keywords: 1-Cinéma; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

DV-made Tibet: Domestic Videos, Elite Films, and the Work of Pema Tseden - Barnett, Robert (DV-Made China: Digital Subjects and Social Transformations after Independent Film, 2015)
In the three decades after 1980, major changes took place in the ways in which culture in Tibet was produced, transmitted, and consumed.¹ These changes, however, were not evidence of the radical transformation often claimed as the result of digitization, but were brought about by earlier forms of technological development. In terms of music and radio, it was the arrival of cheap cassette players and recorders in Tibet in the late 1980s that allowed Tibetans to choose for the first time when to listen and, within the limits allowed by the market and the government, what to listen to (Dhondup
Keywords: 1-Cinéma; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

APPENDIX II: Tibetan Filmography/Videography - Barnett, Robert; Zhen, Zhang; Zito, Angela (DV-Made China: Digital Subjects and Social Transformations after Independent Film, 2015)
Keywords: 1-Cinéma; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Identités diasporiques; _Nettoyé

APPENDIX I: Chinese and Non-Chinese Filmography/Videography - Cho, Ting-Wu; Zhen, Zhang; Zito, Angela (DV-Made China: Digital Subjects and Social Transformations after Independent Film, 2015)
Keywords: 1-Cinéma; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Identités diasporiques; _Nettoyé

Chinese Independent Cinema in the Age of “Digital Distribution” - Gao, Dan (DV-Made China: Digital Subjects and Social Transformations after Independent Film, 2015)
My chapter looks at Chinese independent cinema as an institutionalizing enterprise. In other words, although many filmmakers keep emphasizing the individualistic quality of their agenda or the idiosyncrasy of their film works, independent films have developed things in common, such as certain thematics, addresses, formalistic styles, and modes of production. Their survival is also predicated more and more on shared infrastructures of film communities, distribution agents, and exhibition networks. Of course, this does not mean that the institution of Chinese independent cinema is settled and finalized; it isn’t like a breed of crops circled by impermeable ideological or physical fences.
Keywords: 1-Cinéma; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Identités diasporiques; _Nettoyé

Marking the Body: The Axiographics of the Visible Hidden Camera - Nornes, Abé Mark (DV-Made China: Digital Subjects and Social Transformations after Independent Film, 2015)
This chapter contemplates the ethical dimensions of the specific brand of observational cinema found in China. Because there is no popular understanding of independent documentary—and also because filmmakers almost invariably use amateur video cameras and shoot alone—many subjects are oblivious to the fact that their images are being captured for films being screened around the world. It is in this sense that, while their cameras are perfectly visible, they are also hidden. This enables directors to capture “life unawares,” as if people were being shot by a hidden camera. In this context, directors make the films they want, ignoring the ethical implications of shooting people without being upfront about their intentions or asking for consent. The chapter closely examines a set of films to explore the axiographics of the documentary, in other words how ethics is rendered in the time and space of the moving image.
Keywords: 1-Cinéma; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Chinese Digital Shadows: Hybrid Forms, Bodily Archives, and Transnational Visions - Reynaud, Bérénice (DV-Made China: Digital Subjects and Social Transformations after Independent Film, 2015)
Taking Hao Jie’s Single Man as a case study, this chapter discusses the effect of globalization on independent DV production—a home-grown phenomenon born out of the availability of DV cameras and computer editing software and the spreading of the internet. Starting as a marginalized practice without access to the domestic market, and expressing a desire to saturate the visual field with obfuscated images and to create a counter-archive (a counter-memory of the Chinese people), it attracted international attention, which in turn allowed it to have access to alternative forms of financing as well as the input of foreign talent. The fluidity of digital modes of production also contributed to an eradication of the boundaries between documentary and fiction. Instead, the real divide lies between “the desire for cinema” and “the desire for documentation.”
Keywords: 1-Cinéma; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Documentary Practice and Transnational Feminist Theory - White, Patricia (A Companion to Contemporary Documentary Film, 2015)
This paper looks at five documentaries on activism around ending the practice of female genital cutting (FGC) in Africa. All were made by or in partnership with UK and US producers and are distributed by the New York-based non-profit media arts organization Women Make Movies. By tracing changing political and representational strategies in feminist documentaries on the issue and the varying terms on which the films engage their subjects and address their viewers, the chapter aims to put the specificity of independent documentary formats, practices, and institutions in dialogue with feminist theoretical critiques of the wider discourse on women's human rights. The chapter looks at Kaplan and Grewal's critique of the neo-colonialism of Alice Walker and Pratibha Parmar's Warrior Marks, the observational strategies of Kim Longinotto's The Day I Will Never Forget, the diasporic dimensions of Mrs. Goundo's Daughter and Sarabah, and the visual rhetoric of human rights models in Equality Now's Africa Rising. The cultural field of documentary constitutes a public sphere in which activist and theoretical debate, contested reception, and continually renewed cultural production articulate the productively shifting terms of transnational feminism.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Identités diasporiques; _Nettoyé